Impact of Long-Term Hippotherapy on the Walking Ability of Children With Cerebral Palsy and Quality of Life of Their Caregivers - Mutoh, Tomoko; Mutoh, Tatsushi; Tsubone, Hirokazu; Takada, Makoto; Doumura, Misato; Ihara, Masayo; Shimomura, Hideo; Taki, Yasuyuki; Ihara, Masahiro (Frontiers in Neurology, 2019)
Background: Cerebral palsy (CP) is a permanent motor disorder that occurs at birth or during early infancy. Despite advances in foetal and maternal medicine, the incidence of CP remains high. Hippotherapy has gradually been recognised as an excellent rehabilitation tool for children with CP. However, a scientific basis for how it achieves long-term functional improvements or provides additional benefits to patients’ caregivers remains unknown. Objectives: We performed a prospective trial to determine how hippotherapy affects the gross motor and gait functions in children with CP and how it may also impact the quality of life (QOL) of patients’ caregivers. Methods: In total, 24 children with CP (11 boys, 13 girls; age: 4–14 years; Gross Motor Function Classification System [GMFCS] II-III) underwent a program (30 min/day, once a week) of hippotherapy or day-care recreation (control) over a 1-year intervention and a 3-month follow-up period. Assessment measures used for the children were gait parameters for a 5-m walk test, Gross Motor Function Measure (GMFM)-66, and GMFM dimension-E (GMFM-E). The QOL of the caregivers was estimated using a brief version of the World Health Organization Quality Of Life (WHOQOL-BREF) self-assessment questionnaire. Results: In addition to better GMFM-66 and GMFM-E scores, hippotherapy was associated with increased cadence, step length, and mean acceleration; stabilised horizontal/vertical displacement of patients; and better relationship between the psychological status and QOL of the caregivers than those seen in the control group (p < 0.05). Additionally, the initially improved children’s step length and their caregivers’ psychological QOL domain (particularly in the “positive feeling” facet) tended to be preserved up to the 3-month follow-up. Conclusion: These data suggest that compared with common day-care recreational activities, a 1-year program of once-weekly hippotherapy can improve not only the walking ability of children with CP but also the psychological health and QOL of their caregivers.